2017
DOI: 10.1007/s00586-017-5424-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative total spinal anesthesia as a complication of posterior percutaneous endoscopic cervical discectomy

Abstract: From these two cases, we concluded that the operation of anchoring during PECD should be cautious and standardized, intravenous anesthesia should be chosen to enhance intraoperative anesthesia to prevent intraoperative total spinal anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…From the literature review, total spinal anesthesia can happen during epidural anesthesia, caudal anesthesia, spinal anesthesia, paravertebral block, stellate ganglion block, interscalene brachial blocks, and other regional anesthesia techniques performed at or near to the vertebral column. The clinical manifestations are often characterized by a sudden decrease in blood pressure, rapidly increasing motor block, temporary loss of breathing, loss of consciousness, dilated pupils, apnea, and even cardiac arrest [ [8] , [9] , [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%
“…From the literature review, total spinal anesthesia can happen during epidural anesthesia, caudal anesthesia, spinal anesthesia, paravertebral block, stellate ganglion block, interscalene brachial blocks, and other regional anesthesia techniques performed at or near to the vertebral column. The clinical manifestations are often characterized by a sudden decrease in blood pressure, rapidly increasing motor block, temporary loss of breathing, loss of consciousness, dilated pupils, apnea, and even cardiac arrest [ [8] , [9] , [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors established that highly increased cervical epidural pressure by continuous saline irrigation was the main cause (39). Two cases of approach-related intraoperative total spinal anesthesia during posterior PECD were reported by Wu et al (40). Perforation on C6 lamina with the spinal needle during the approach lead anesthetics went through the iatrogenic hole to subarachnoid space.…”
Section: Complicationsmentioning
confidence: 99%
“…To date, numerous studies have reported p-PECD for the management of cervical disorders (19) (13,(15)(16)(17)(18)(19)(20)(21)(23)(24)(25)(26)(27) and have studied the inner diameter of the p-PECD working channel, ranging from 3.7 mm to 6.9 mm (17,22,28). However, no studies have been conducted to compare the clinical outcomes of the application of a 3.7 mm endoscope and 6.9 mm endoscope in CDH patients.…”
Section: Introductionmentioning
confidence: 99%